1981
DOI: 10.1128/iai.32.1.404-406.1981
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Seminal Plasma on Chlamydia trachomatis Strain LB-1 in Cell Culture

Abstract: Human seminal plasma inhibited formation of strain LB-1 chlamydial inclusions in McCoy cells proportional to the concentration of seminal plasma added after chlamydial adsorption.Chlamydia are among the most common sexually transmitted organisms and are probably responsible for at least one-half of the cases of nongonococcal urethritis in males. We questioned whether genital secretions might influence the infectivity of such agents (6) or the susceptibility to infection of the host cells. We describe here the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1983
1983
2002
2002

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 4 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…During the last 2 decades there have been many valuable studies of chronic bacterial prostatitis. These efforts have improved our understanding of both specific immunological factors and nonspecific host defenses of the male lower urogenital tract, such as pH and the prostatic antibacterial factor (3,4,6,8,14,17).…”
Section: Discussionmentioning
confidence: 99%
“…During the last 2 decades there have been many valuable studies of chronic bacterial prostatitis. These efforts have improved our understanding of both specific immunological factors and nonspecific host defenses of the male lower urogenital tract, such as pH and the prostatic antibacterial factor (3,4,6,8,14,17).…”
Section: Discussionmentioning
confidence: 99%
“…The definitive demonstration of a chlamydial aetiology is based on the isolation of C. trachomatis from the mucous membranes. This task may be difficult since it has been demonstrated that seminal factors have some undetermined inhibitory effect on chlamydial inclusion formation in cell culture (a method used for isolation of C. trachomatis) (Mirdh et al 1980;Hanna et al 1981).…”
Section: Discussionmentioning
confidence: 99%
“…concluded that PAF is free zinc. In addition to bactericidal activity against gram‐negative organisms, zinc may inhibit the growth of viruses, 8,9 yeats, 10 protozoa 11 and Chlamydia trachomatis 12,13 …”
Section: Introductionmentioning
confidence: 99%